Cultural adaptation and validation of the Brazilian Version of the Patient Activation Measure-22 items - Cristiane Martins Cunha; Eliane Nepomuceno; Rafaela de Oliveira Manzato; Débora Cristine Prévide Teixeira da Cunha; Dirceu da Silva; Rosana Aparecida Spadoti Dantas
ABSTRACT Objective: To adapt and validate the Patient Activation Measure (PAM22) in a sample of Brazilians with chronic diseases under outpatient monitoring. Method: Adaptation process comprises translation, back translation, analysis by a committee of judges, semantic analysis, and pre-test. Psychometric validation was performed with 513 individuals. Construct validity was analyzed through Pearson's correlation, Student's t-test and Structural Equation Modeling; reliability was assessed by the intraclass correlation coefficient and Cronbach's Alpha. Results: The internal consistency was adequate and test-retest reliability was low to moderate (p < 0.05). Validity evidence was found on the convergent construct, with statistically significant correlations between measures of activation, self-esteem, anxiety, depression, and health status. The one-dimensionality of the theoretical model was not confirmed in the adapted version. Conclusion: Results have shown that the adapted version is reliable and valid, although the theoretical model cannot be explained in a single dimension.